Retcam fluorescein angiography findings in eyes with advanced retinoblastoma. Issue 12 (22nd July 2014) - Kim, Jonathan W; Ngai, Lynn K; Sadda, Srinivas; Murakami, Yohko; Lee, Diana K; Murphree, A Linn
Abstract : Purpose: To characterise the fluorescein angiogram (FA) findings of eyes with advanced retinoblastoma evaluated with the Retcam contact fundus camera. Methods: A retrospective case series was performed on all new retinoblastoma patients evaluated with Retcam FA between 2000 and 2012. Inclusion criteria included (1) patients with advanced retinoblastoma (group D or E), (2) eyes studied with early, mid-phase and late-phase Retcam FA photographs and (3) no prior treatment. Results: A total of 100 eyes fulfilling the inclusion criteria were identified. For the 47 group D eyes, FA findings included iris neovascularisation (10/47), large retinal vessel dilatation (46/47), small retinal vessel changes (35/47) and retinal venous leakage (20/47). Among the 53 group E eyes, FA findings included iris neovascularisation (45/53), large retinal vessel dilatation (43/53), small retinal vessel changes (37/53) and vascular abnormalities at multiple levels (11/53). Conclusions: Advanced intraocular retinoblastoma is associated with multiple retinal vascular abnormalities on Retcam FA. These findings may be helpful in defining the extent of disease and distinguishing this tumour from other paediatric ocular conditions. Key clinical findings were subclinical iris neovascularisation, a variety of small vessel changes, intrinsic tumour vessels and retinal venous leakage. Retcam FA was not found to be clinically useful after 3 min.